2019
DOI: 10.1186/s13063-019-3381-9
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive therapy versus exposure and response prevention for obsessive-compulsive disorder: study protocol for a randomized controlled trial

Abstract: Background The recommended psychological treatment of choice for obsessive-compulsive disorder (OCD) is exposure with response prevention (ERP). However, recovery rates are relatively modest, so better treatments are needed. This superiority study aims to explore the relative efficacy of metacognitive therapy (MCT), a new form of cognitive therapy based on the metacognitive model of OCD. Design and method In a randomized controlled trial, we will compare MCT with ERP. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…However, the strength of efficacy for both treatments appeared to be less than that generally found with ERP (Rupp et al, 2019). Despite promising results for metacognitive therapy in patients with OCD in case series, a full controlled trial has yet to be performed (Melchior et al, 2019).…”
Section: Novel Forms Of Psychotherapymentioning
confidence: 89%
“…However, the strength of efficacy for both treatments appeared to be less than that generally found with ERP (Rupp et al, 2019). Despite promising results for metacognitive therapy in patients with OCD in case series, a full controlled trial has yet to be performed (Melchior et al, 2019).…”
Section: Novel Forms Of Psychotherapymentioning
confidence: 89%
“…Despite CBT providing significant benefits in the treatment of OCD, treatment remains below optimal levels in a significant proportion of patients. 16 Furthermore, it has been reported that in reality, only 25% of the patients remain completely asymptomatic. 17 …”
Section: Introductionmentioning
confidence: 99%
“…According to Wells’s model, 2 metacognitive steps lead to the occurrence and continuation of OCD. 16 In the first step, obsessions occur through metacognitive beliefs that cause intrusions to be interpreted as dangerous and harmful 29 because obsessional intrusions are mixed with events, actions, and objects, and this situation is named as “fusion.” In Wells’s theory, the system works as follows: when the thought-event, thought-action, thought-object fusion is activated, patient with OCD begins to give importance to their intrusions and shows a trend to interpret these intrusions as threatful. 30 At this point, second step is stimulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Y-BOCS/CY-BOCS score range of severity for patients who have both obsession and compulsions was categorized as follows: mild OCD (< 13); moderate OCD (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), severe OCD (> 22) [30] (Fig. 1: Flowchart of the identi cation of the included studies).…”
mentioning
confidence: 99%